2015
DOI: 10.1039/c5ra08335d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effects of activated carbon particles on gas hydrate formation at oil–water interfaces

Abstract: The inhibition effects of activated carbon particles on hydrate growth at water and oil interfaces was studied. Significantly reduced hydrate growth was seen in the presence of 0.5 wt% AC particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…In the next subsections, some details are provided to explain these phenomena. Presence of activated carbon particles ↓ ↓ [51] Presence of free resins, biding resins, and residual Asphaltenes NA ↓ [141] where ↑: increase; ↓: decrease; NA: Not Acknowledge.…”
Section: Kinetics Of Cph Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next subsections, some details are provided to explain these phenomena. Presence of activated carbon particles ↓ ↓ [51] Presence of free resins, biding resins, and residual Asphaltenes NA ↓ [141] where ↑: increase; ↓: decrease; NA: Not Acknowledge.…”
Section: Kinetics Of Cph Formationmentioning
confidence: 99%
“…Note that CP act as a hydrate promoter for other applications, such as carbon capture, as described in detail by Herri et al [22], or Zheng et al [47]. It is a co-guest used to milder hydrate formation conditions when combined to other molecules such as N 2 [40,[48][49][50], C 3 H 8 [51], CO 2 [48,49,[52][53][54], CH 4 [40,49,55,56], or H 2 S [56]. Thus, the use of cyclopentane hydrates (CPH) for a combined gas capture and desalination process could be applicable and probably more interesting energetically.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, when hydrophobic nanoparticles are at the oil-water interface, the migration of gas and liquid molecules will be prevented, thus inhibiting hydrate formation. 23,24 For hydrophilic nanoparticles, some studies have found that they can also promote hydrate formation. 25 But molecular dynamics simulations show that hydrates are difficult to form on hydrophilic solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, the inhibition effect of silica nanoparticles and carbon particles on CP hydrate formation was characterized. 23,24 Because the particles at the water−oil interface prevent diffusion or contact of the CP hydrate slurry, formation and growth of CP hydrates can be delayed. It should be noted that a few earlier studies reported fast formation of methane hydrates by dispersing water into the hydrophobic silica nanoparticles (dry water) to increase the contact area between water and methane gas.…”
Section: ■ Introductionmentioning
confidence: 99%